Pertimbangan Besaran Upah Minimum Kabupaten Banyumas Oleh Dewan Pengupahan Kabupaten Banyumas - Haris Kusumawardana; Agus Djatmiko; Wahyu Hariadi (Wijayakusuma Law Review, 2024)
Abstract This paper is entitled Considerations of the Banyumas Regency Minimum Wage Amount by the Banyumas Regency Wage Council. This study aims to determine the process of implementing the Banyumas Regency minimum wage in 2023. This research is a sociological juridical research with the subject of study by the Banyumas Regency Manpower, Cooperatives and SMEs Service. The aim of this research is to build synergy between the Banyumas Regency Wage Council and the obstacles in determining the minimum wage in Banyumas Regency. Wages are income received by workers in the form of money, which includes not only wages/salaries, but also overtime and allowances received on a regular basis, excluding holiday allowances which are annual, quarterly, and other allowances which are not routine. Wages are all kinds of payments arising from work contracts, regardless of the type of work, which are a form of income received by workers as compensation for the work they do. To determine the district minimum wage in accordance with community standards, the district minimum wage is determined by the government, namely the district Department of Manpower, Cooperatives and Small and Medium Enterprises. Keywords: Wages, Wage Council, Banyumas Regency Abstrak Karya tulis ini berjudul Pertimbangan Besaran Upah Minimum Kabupaten Banyumas Oleh Dewan Pengupahan Kabupaten Banyumas. Studi ini bertujuan untuk mengetahui proses pelaksanaan upah minimum Kabupaten Banyumas Tahun 2023. Penelitian ini merupakan penelitian yuridis sosiologis dengan subjek kajian Dinas Tenaga Kerja, Koperasi dan UKM Kabupaten Banyumas. Tujuan dari penelitian ini adalah untuk membangun sinergitas dari Dewan Pengupahan Kabupaten Banyumas dan kendala dalam menetapkan besaran upah minimum di Kabupaten Banyumas. Upah merupakan pendapatan yang diterima tenaga kerja dalam bentuk uang, yang mencakup bukan hanya upah/ gaji, tetapi juga lembur dan tunjangan tunjangan yang diterima secara rutin atau reguler, tidak termasuk Tunjangan Hari Raya yang bersifat tahunan, kwartalan, tunjangan-tunjangan lain yang bersifat tidak rutin. Upah adalah segala macam pembayaran yang timbul dari kontrak kerja, terlepas dari jenis pekerjaannya yang merupakan bentuk penghasilan yang diterima oleh pekerja sebagai imbalan atas pekerjaan yang dilakukannya. Untuk menentukan penetapan upah minimum kabupaten agar sesuai dengan standar kebutuan masyarakat, maka upah minimum kabupaten ditentukan oleh pemerintah yaitu Dinas Tenaga Kerja, Koperasi dan Usaha Kecil dan Menengah kabupaten. Kata kunci: Upah, Dewan Pengupahan, Kabupaten Banyumas